Enrollment in Hispanic Serving Institutions as a Moderator of the Relationship between Drinking Norms and Quantity of Alcohol use among Hispanic College Students. Issue 3 (July 2015) - Vaughan, Ellen L.; Chang, Tiffany K.; Escobar, Oscar S.; de Dios, Marcel A.
Background: Hispanic college students represent a growing proportion of the college population. Studies have found that an individual's perception of the drinking of others is linked to one's own personal use and that college students frequently overestimate the drinking of their peers. The current study builds on previous college student drinking literature by examining the influence that attending a Hispanic-serving institution (HSI) has on the personal alcohol use and perception of peers' drinking norms among Hispanic college students. Methods: This secondary data analysis utilized data from the American College Health Association's National College Health Assessment. Participants were self-identified Hispanics between the ages of 18 and 25 ( N = 4336). Results: Results indicated that there was a significant interaction between attending an HSI and the perception of the number of drinks of a typical student. Specifically, the perception of others' drinking was more strongly linked to personal drinking for students in non-Hispanic serving institutions. Conclusions: The protective effect of attending a Hispanic-serving institution may be related to a more culturally affirming college environment.